64‐2: Ultra‐Thin RGB Mini‐LED Backlight for High‐end Professional Liquid Crystal Displays. Issue 1 (28th June 2022) - Meng, Xianqin; Chen, Xiaochuan; Peng, Weiting; Zhang, Shunhang; He, Wei; Sun, Shuang; Ling, Qiuyu; Wang, Wei; Liang, Pengxia; Tan, Qiaofeng; Dong, Xue
Abstract : This report discusses a glass based ultra‐thin Red, Green and Blue Mini‐LED direct back light for high‐end professional liquid crystal displays. In this work, a gradient reflected pattern combined Mini‐LED driving lines reflect light scattering between the patterns and back reflector of back light unit, and therefore enlarge Mini‐LED optical length. A group of a red, green and red Mini‐LED is using to generate white for display, replacing a 0.3–0.5mm thick color changing film. The total thickness of Mini‐LED direct back light is reduced to 1.595mm when the Mini‐LED pitch is about 4.75mm. This direct back light can realize high‐dynamic range to improving display quality without cost consumption and then extend lifetime liquid crystal display lifetime in coming decent years.